The Ethical Environment of Tax Practitioners: Western Australian Evidence - Marshall, Rex L. (Journal of business ethics, 1998)
This study examines Australian tax agents' perceptions of the ethical environment in which they practice, within the context of an income tax system based on self-assessment principles. The research identifies and ranks an inventory of ethical issues in terms of perceived frequency of occurrence and importance to Western Australian tax agents. In addition, the extent and influence of ethical concerns in the profession are evaluated., The study has determined that the most frequently cited ethical issue is the failure to make reasonable enquiries where information or documentation provided by a client appears to be inaccurate or incomplete. The most important ethical problem is a failure to ensure confidentiality with regard to privileged client information. When the frequency of occurrence and importance means are compared, inadequate technical competence, failure to make reasonable enquiries/conduct research, continuing to act for a client where there is incorrect information, and conflicts in distinguishing between tax planning and tax avoidance emerge as the ‘high frequency/high importance’ issues. Although acknowledging the potential for unethical actions in tax practice, Western Australian tax agents consider that they carry out their professional activities within an ethical environment.